The brass verdict : [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel., 2008)
Just as defense attorney Mickey Haller's life is going back to normal, a Hollywood lawyer named Jerry Vincent is murdered and Mickey takes on the case of the accused, which could take his career into the big leagues. Haller learns that the killer may be looking for him and Harry Bosch. With danger mounting, Bosch and Haller decide to work together.